Musical Crossing Between The Balinese Gamelan and Gendang Beleq in Lombok West of Nusa Tenggara - ketut supartha (UPT Pusat Penerbitan LP2MPP ISI Bali, 2021)
Study on the Sasak and Balinese music are very limited. This is caused to the lack of cultural understanding between the Balinese and Sasak people. However, the historical ties between those people already rooted in the past of their history. The aims of this paper is to highlight the issues on to what estend the music could play a significant role in integrating those ethnic groups in harmonious and peaceful ways. The pertinent question that need to be addressed in this paper: firstly how is the musical crossing form ,between Balinese gamelan and the Gendang Beleq in Lombok, secondly, how the Balinese and the Sasak began to integrate one to each other. The method used in this research is qualitative with acquired data sources in the field based on the results of interviews of some informant. Theory used in analyzing the problem is ethnomusicology theory by Alan P Marriam.